Toxicology and the biological role of methanol and ethanol: Current view - Pohanka, Miroslav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND: Alcohol variants such as ethanol and methanol are simple organic compounds widely used in foods, pharmaceuticals, chemical synthesis, etc. Both are becoming an emerging health problem; abuse of ethanol containing beverages can lead to disparate health problems and methanol is highly toxic and unfit for consumption. METHODS AND RESULTS: This review summarizes the basic knowledge about ethanol and methanol toxicity, the effect mechanism on the body, the current care of poisoned individuals and the implication of alcohols in the development of diseases. Alcohol related dementia, stroke, metabolic syndrome and hepatitis are discussed as well. Besides ethanol, methanol toxicity and its biodegradation pathways are addressed. CONCLUSIONS: The impact of ethanol and methanol on the body is shown as case reports, along with a discussion on the possible implication of alcohol in Alzheimer's disease and antidotal therapy for methanol poisoning. The role of ethanol in cancer and degenerative disorders seems to be underestimated given the current knowledge. Treatment in case of poisoning is another issue that remains unresolved even though effective protocols and drugs exist.
Keywords: Aldehyde Dehydrogenase; Ethanol; Alcoholic Beverages; aldehyddehydrogenasa; methanol; Antidotes; Alcoholism; Humans; Receptors, Cell Surface; lidé; Methanol; antidota; alkoholismus; Alcohol Dehydrogenase; receptory buněčného povrchu; ethanol; alkoholdehydrogenasa; alkoholické nápoje